Road Safety for Persons with Disabilities in Palembang - Nurussama; Rizki Fitri Amalia (Journal of Infrastructure Policy and Management (JIPM), 2020)
According to the Ministry of Social Affairs No. 178/HUK/2016, there are 245,716 persons with care home-based social welfare problems spread across Indonesia and 5,824 care homes throughout the country. The regional governments, assisted by the central government, build public facilities that can accommodate the needs of citizens with disabilities who are often neglected. One of concrete results of development is when there is equitable development where all elements of the population can feel the impact of the development, including the disability community. Palembang as an organizer of international events still has problems with transportation and facilities for road users. The purpose of this study is to analyze the effect of safety of facilities and infrastructure on public transportation users in Palembang (a case study of persons with disabilities in Palembang). The methods used are quantitative and qualitative and the sampling method used is purposive sampling and 148 saturated samples. Based on the results of the study, it can be concluded that all variables of facilities and infrastructure are proven to be significant, but several variables such as road facilities, pedestrian bridges (JPO) have weak relationships, and persons with disabilities are considerably helped by Trans Musi conductors. Transmission conductors are considered very attentive to the needs of passengers from waiting for arrival to stop. The results of this study are expected to contribute to improving facilities and infrastructure, especially for persons with disabilities.